Personality characteristics of wives of gamma and delta alcoholics - Altschuler, Jennifer (Department of Psychology, 2023)
40 wives of first admission alcoholics admitted to an alcoholic clinic and a mental hospital were examined and classified into two groups, on the basis of their husband's pattern of drinking, 17 falling into gamma and 23 into delta categories. Subjects were tested on Cattell 's 16PF, Fould1 s Hostility Questionnaire and Gough and Heilbrun's Adjective Check List. In addition, information as regards family background, drinking history and pattern of drinking was obtained in interviews. No significant grouping correspondent with the gamma/delta classification was found with any of the psychological tests or case history data, other than wives of gamma alcoholics tending to marry men whom at the outset of marriage already had a drinking problem. Multidimensional scaling techniques showed there to be some grouping operative within the total sample, corresponding with socio-economic class. Subjects falling into the lower socio-economic classes appeared to be mare hostile, anxious and neurotic than those in the higher classes. Although some heterogeneity thus appeared operative amongst wives of alcoholics, this did not correspond with their husband1 s pattern of drinking.